Moretvm 70: An Emendation. Issue 1 (1st January 2018) - Kayachev, Boris
Abstract : I argue that Moretum 70 uicinosque apte cura summittere riuos should be restored as uicinosque apte cultis [Heyne] inducere [scripsi] riuos .